Антропологічна спрямованість порівняння у науковому дискурсі - Шаля, О.І. (Центр наукових досліджень та викладання іноземних мов НАН України, 2009)
Using G. Fauconnier’s mental spaces theory, we tackle personified inanimate objects in scientific discourse. To this end, we apply one type of mapping operations, a projection mapping, to project the structure from the source domain – animated world onto the target domain – inanimate world.